Case of a Rare Variant of Deep Cerebral Venous Thrombosis after Treatment with Norgestrel-Ethinyl Estradiol - Bhaskar, Swapna; Bhat, Alevoor Rajaram; Rao, Badakare Chidamber (Indian Journal of Pharmacy Practice)
Cerebral Venous Thrombosis (CVT) is a rare but potentially life-threatening disease characterized by thrombosis of the cerebral venous system, frequently seen in young population. Use of Oral Contraceptive Pills (OCP) is one of the major risk factors for CVT in women along with pregnancy, collagen vascular diseases and other hypercoagulable states. The symptoms and signs of CVT can be quite vague like headache and requires quick assessment and investigations like magnetic resonance imaging with angiogram for diagnosis. Although complete recovery is possible with early treatment, mortality can be seen in as much as 15% of cases if treatment is delayed. This article discusses a very rare variety of CVT and reviews the epidemiology, risk factors, clinical presentation, diagnosis and management of CVT.
Keywords: Oral Contraceptive Pills; Cerebral venous thrombosis; PCOD.